Moving Target - Eason, Lynette (Grand Rapids, Michigan : Revell, a division of Baker Publishing Group, 2017)
"When Maddy McKay and Quinn Holcombe don't show up for Quinn's surprise birthday party, his friends know that something is very wrong. Their search turns up little beyond evidence that Quinn and Maddy just decided to take off for a long overdue vacation. But it soon becomes apparent that they did not leave of their own accord"--Amazon.com.
Keywords: Bodyguards -- Fiction; Missing persons -- Fiction; Christian fiction; Thrillers (Fiction); Detective and mystery fiction